Québec’s Bill 96: A Case Study of Indigenous Cultural and Political Dispossession - Kredl, Katya (Journal of Critical Race Inquiry)

(untitled) (Queen's University, 2026)
This article examines Bill 96 (now Law 14; 2022), a language law enforcing French as the official language of Québec, in relation to language hierarchization and Indigenous dispossession. While this bill impacts all non-French speaking individuals in Québec, it carries especially important implications for the Indigenous Peoples residing on this territory whose languages are already endangered. In this article, I explore Bill 96 as an extension of settler colonialism that legitimizes white settlers as founders and that assimilates through language. Using previous Canadian language laws as a guide, I demonstrate the dangers of exclusionary language policies. From insular decision-making strategies to strict legal enforcement, these types of policies are grounded in dominant, colonial logic and have the potential to eradicate vulnerable cultures. Using political discourse analysis (PDA), I argue that this bill ultimately threatens the survival of Indigenous cultural and political structures in Québec. Finally, I reflect on Indigenous languages as a tool of refusal to settler colonialism.